Participation of Latin America and Ecuador in the Creation of Enterprises in the Orange Economy - Morales-Molina, Tania (2023)
Home Advances in Tourism, Technology and Systems Chapter Participation of Latin America and Ecuador in the Creation of Enterprises in the Orange Economy Tania Morales Molina, Chabely Figueredo Morales, Ana Graciela Guédez Mujíca, Geri Belén Bucheli Vásquez & Alejandro Chaviano Quesada Chapter First Online: 05 October 2023 69 Accesses Part of the Smart Innovation, Systems and Technologies book series (SIST,volume 345) Abstract The orange economy is a development model in which cultural diversity and creativity are pillars of social and economic transformation. This sector is mainly related to the generation of ideas and intellectual property and includes areas such as performing arts, cinema, tourism, design, advertising, fashion, music, visual arts, architecture, technological services, among others. The objective of this research is to analyze the public programs implemented in Latin America and Ecuador as a special focus on the creation of enterprises in the orange economy. The methodology used in this research work is qualitative—descriptive, using secondary sources such as economic reports, state reports, and public institutions. The results of the research show initiatives at both the private and governmental levels to promote the orange economy in the country. The main conclusions are that Latin America and Ecuador as a special focus, need to promote training opportunities especially creative ideas associated with technology, develop observatories of the creative industries and thus enhance entrepreneurship under this heading to ensure its sustainability over time, as well as replicate successful initiatives of developed countries.